Outbreak of Amazonian Toxoplasmosis: A One Health Investigation in a Remote Amerindian Community - Blaizot, Romain; Nabet, Cécile; Laghoe, Laure; Faivre, Benjamin; Escotte-Binet, Sandie; Djossou, Felix; Mosnier, Emilie; Henaff, Fanny; Blanchet, Denis; Mercier, Aurélien; Dardé, Marie-Laure; Villena, Isabelle; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Toxoplasma gondii is a parasite of worldwide importance but its burden in indigenous communities remains unclear. In French Guiana, atypical strains of T. gondii originating from a rainforest wild cycle have been linked to severe infections in humans. These cases of Amazonian Toxoplasmosis are sporadic and outbreaks are rarely described. We report on the investigation of an outbreak of acute toxoplasmosis in a remote Amerindian village. We discuss the causes and consequences of this emergence. Methods: Inhabitants from nine households were tested for T. gondii antibodies and parasite DNA by PCR when appropriate. Samples of water, cat feces and cat rectal swabs, soil and meat were tested for T. gondii DNA by PCR. Positive PCR samples with sufficient DNA amount were genotyped using 15 microsatellite markers. Results: Between early May and late June 2017, out of 54 tested inhabitants, 20 cases were serologically confirmed. A foetus infected at gestational week 10 died but other cases were mild. Four patients tested positive for parasite DNA and two identical strains belonging to an atypical genotype could be isolated from unrelated patients. While domestic cats had recently appeared in the vicinity, most families drank water from unsafe sources. Parasite DNA was recovered from one water sample and nine soil samples. Meat tested positive in three samples, including wild and industrialized meat. Conclusions: The recent domestication of cats probably enhanced the wild cycle of T. gondii in a village where fixed habitations along with unsafe sources of water paved the way for the emergence of human toxoplasmosis. The burden of T. gondii should be properly studied in other remote populations. Public health actions such as eradication of cats and epidemiological surveillance of acute toxoplasmosis should be implemented.